A subordinação dos trabalhadores em plataformas digitais - Andreoni, Elisa Maria Secco (2022)
The subject of subordination in work relationships gained expression with the creation of the first labor laws, which was implemented after the historic landmark of the First Industrial Revolution, when there was a profound change in the form of human work. However, since the beginning of society, work has been part of human relationships: history shows that, in the first social formations, human beings worked submissively to others. Over the centuries, the forms of work evolved, and with the advent of Enlightenment ideals, it has come to free and, therefore, salaried work. From the Industrial Revolution onwards, there was a gradual concentration of workers in manufactures and factories, radically changing the way in which work was performed. In this way, with the insertion of workers in the company’s organization, who started to integrate it by their own will (even if liable to the orders of the service taker), the concept of subordination arises, a legal element of the traditional employment relationship that became disciplined with the creation of labor laws. With the creation of the legal concept of subordination, when the first employment contracts appeared, the questions related to the topic were limited to revealing the nature of subordination existing in employee contracts – whether it would be technical, economic or legal. According to doctrine and jurisprudence, the latter meaning of subordination prevailed, but its role as a requirement for employment relationships was not yet questioned. However, with the emergence of new ways of working, propagated mainly by subsequent technological revolutions, working methods have also changed. For this reason, the element of subordination, so important in the context of the employment contract, has been a constant object of studies. In line with these discussions, the present work aims to analyze how new technologies have transformed work models and whether they have affected the concept of subordination inherent to the traditional form of employment contract. More specifically, it is interesting to verify if workers on digital platforms, subject to the dictates of the algorithm, differ from workers with an employment relationship, in order to, from that, reflect on what legal protection should be given to them. The discussion of this topic is necessary, insofar as, if, on the one hand, the traditional forms of employment contract are losing their character, in the view of economists and some theorists, on the other hand, workers on digital platforms carry out their activities with various elements of the traditional employment contract (including being subject to the rules of such platforms), but are outside the protection of labor law rules